INOVASI LAYANAN SEBAGAI VARIABEL PEMEDIASI HUBUNGAN ANTARA BUDAYA LAYANAN DAN KINERJA ORGANISASI - Sularsih Anggarawati; Fachri Saputra (UNIB Press, 2019)
Nowadays, public sector organizations have been exposed with tremendous pressure toadapt to significant change from the external environment (Valle, 1999). The dynamismof public service needs that are getting better is a demand and necessity at this time,because of technological developments, consumer preferences, fast service, transparentand simple bureaucratic systems, and good service governance are demands for thepublic as end consumers. Problems related to the complicated bureaucracy in publicsector organizations will be overcome if the organization has a good service culture.The attitude and behavior of employees is a reflection of the service culture instilled bythe organization. A good service culture will support service innovation by employeeswhich in turn impacts on organizational performance. Therefore, service culture isbelieved to have a significant effect on shaping employee service performance inIndonesian public agencies.This study is a quantitative descriptive study that aims to confirm the relationshipbetween variables in empirical research for the reliability testing of a theory. This studywill only be conducted at one specific time which will show a phenomenon to answer theresearch questions to be studied, so that it uses a cross sectional research design.Respondent samples used in this study were 250 respondents. To answer the researchobjectives, researchers used Structural Equation Modeling as a data analysis tool. Dataanalysis was performed using PLS Graph 3.0. The results of the study found that one ofthe three hypotheses proposed proved significant in this study. The hypothesis thatproved significant was the effect of service innovation on organizational performance,while the influence of service culture on service innovation and organizationalperformance was not proven in this study.